Transboundary Externalities and Reciprocal Taxes: A Differential Game Approach - Charles F. Mason (Center for Economic Studies and ifo Institute (CESifo), 2017)
I investigate the interaction between a country that imports a commodity whose production contributes to a stock pollution, such as electricity, from a country that produces that commodity. If the transboundary externality is priced improperly, the application of a feed-in tariff or border tax adjustment can provide an indirect policy instrument. But the imposition of such a tariff or tax creates an incentive for the producing country to deploy some sort of pollution controlling instrument. This, in turn, creates a strategic interaction between the two countries. Because the externality is inked to a stock pollutant, this strategic interaction will play out over time, which induces a dynamic game. In this modeling context, I describe the nature of the strategic interaction, and characterize the Markov-perfect equilibrium.
Keywords: C73; Q54; Q58; 330; transboundary pollution; differential game; tariff; tax